Utilization of Fish Meal and Fish Oil from Smoked Salmon By-Products in Juvenile Striped Bass (Morone saxatilis) Feeds: Growth Performance, Nutritional Composition, and Shelf-Life Assessment of Upcycled Ingredients - Connor Neagle; Michael O. Frinsko; Ryan Kelly; Steven G. Hall; Benjamin J. Reading; Alexander Chouljenko; Greg Bolton; Michael Joseph (Fishes, 2025)
Fish meal (FM) and fish oil (FO) are vital components commonly used in feed formulations. However, their supply, which generally comes from capture fisheries, is being exhausted, necessitating the exploration of sustainable alternatives. In a two-part study, the first part evaluated the FM and FO derived from smoked salmon by-product (SSBP) over a 12-week accelerated shelf-life test, comparing their lipid oxidation, amino acid, and fatty acid profiles to those of commercial whitefish meal and oil. In the second part, the SSBP FM and FO were then included in three experimental feeds at 25%, 50%, and 100% inclusion levels. These feeds were tested on juvenile striped bass (Morone saxatilis) cultured in a recirculating aquaculture system (RAS). The results indicated that the quality of SSBP FM and FO was lower than the commercial product (less amino acids (23.98% vs. 60.30%) and omega-3 fatty acids (9.46% vs. 26.6%), respectively). SSBP FO exhibited high initial peroxide value (21.00 ± 0.00 meq/kg oil), with gradually increasing total oxidation value and p-Anisidine value during storage. Regarding the feeding trial, all fish showed signs of Mycobacterium marinum infection after one month. While there was no significant difference in feed palatability (p > 0.8559), the feed conversion ratio was less efficient for the 100% SSBP feed (1.44 ± 0.14) compared to commercial feed (1.36 ± 0.13), but these differences were not statistically significant. This study suggests that SSBP FM and FO can be used as supplements at lower levels (25% and 50%) without negatively affecting growth, feed efficiency, or survival. Our findings may be useful for enabling beneficial collaborations between smoked salmon processors, feed manufacturers, and striped bass farmers, therefore contributing to sustainability in aquaculture practices.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)